Design of village e-budgeting information systems - Indratno, Imam; Fardani, Irland; Kuntoro, Sena Hari (Journal of Governance and Accountability Studies, 2024)
Purpose: This study aims to design the flow of the e-budgeting system to develop the village financial system, as well as to increase transparency and accountability of the web-based budget system and minimize the occurrence of corruption loopholes in the village. Method: The design system uses the waterfall method to analyze a model systematically. The model development step starts with the design of the system, database, menu structure, and interface. The design of the e-budget information system is built using PHP and MySQL programming in the form of web-based applications. Results: This study developed a web-based e-budgeting application using the waterfall method to manage village finances. The online system increases flexibility, allowing access from any device. It runs smoothly on computers, with all menus functioning as designed, and is expected to simplify village financial management. Limitations: The researchers’ capability in designing the system is not optimal, as the researchers do not have the basis of informatics engineering, so the results obtained and delivered are not too detailed. Contributions: This system is expected to be useful to facilitate the process of financial management at the village government level. Novelty: The novelty of this study lies in the design of a village e-budgeting system with features like automatic Standard Unit Price calculation, automated tax management, and tracking of village income (PADes) for transparency. This application aims to enhance financial management, ensuring transparency and accountability in the village.